An introduction to the science of epigenetics - Thapa, JB (Journal of Pathology of Nepal, 2013)
Epigenetics has emerged as an important new discipline. This review provides deeper insights into understanding basic defects in methylation, histone modification, and RNA induced silencing of tumours. These mechanisms have important diagnostic and therapeutic implications for many tumours and diseases. New anti-epigenetic based drug therapies have been developed and drug trials are underway. The future will see further developments in this field. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 408-410 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7870